Sorption and thermodynamic study of nitrate removal by using Amberlite IRA 900 (AI900) resin - Aimi Asyiqin, Abu Kassim; Norhayati, Abdullah (Elsevier Ltd, 2021)
This paper presents the efficiency removal and thermodynamics studies of nitrates by using ion exchange resin, Amberlite IRA 900-Cl (AI900). The effect of experimental factors of contact time resin (1–6 h), resin dosage resin (1–6 g), initial concentration of nitrate influent in the range between 20 and 250 mg/L and temperature between 25 and 65 °C were studied by using a batch sorption method. From the overall study, the data clearly demonstrated that the optimum temperature for the nitrate ions were removed was at 25℃ as the sorption of nitrate decreased when the temperature increased. The sorption managed to obtain 85% removal of nitrates from bulk concentration by using 2 g of AI900 resin in 1-hour contact time. While increasing the contact time of resin until 6 h in 1 g resin and increasing the amount of resin to 6 g of AI900 resin in 1-hour contact time, the adsorption capacity managed to rise at 98 and 97%, respectively. AI900 resin demonstrated an exothermic and spontaneous process of nitrate removal at the varied temperatures as both enthalpy (ΔH°) and entropy (ΔS°) showed negative signs at −26.801 kJ/mol and −43 J/K∙mol respectively. The sorption was feasible and favored at low temperature as the Gibb energy (ΔG°) showed negative sign and decreased with the increasing temperature.